Triboelectric Nanogenerator Based Self-Powered Tilt Sensor - Faisal Iqbal; Muhammad Shafi; Muhammad Irfan Khattak; Aamir Nawaz (Tehnički Vjesnik, 2018)
This work focuses on the fabrication and evaluation of triboelectric nanogenerator (TENG) based self-powered tilt sensor. The proposed fabricated structure is composed of polydimethylsiloxane (PDMS), steel ball, gold (Au) as electrode and circular ring housing. A specific configuration of electrodes was used to measure the tilt at different angles. FEM simulations were used to verify the electric potential at the electrodes at different angles. The outputs of the fabricated sensor were measured at different angles from 0 to 360°. A sensitivity of 254 mV/rad is obtained in single axis. The TENG based tilt sensor generates an open circuit voltage of 450 mV at 10 MΩ.